Horseshoe kidney with triple renal arteries and an aberrant right testicular artery in a male cadaver: case report - Dibakar Borthakur; Ritu Sehgal; Neerja Rani; Rajesh Kumar; Rakesh Kumar; Rima Dada (Jornal Vascular Brasileiro)
Abstract Horseshoe kidney (HSK) is a rare congenital malformation of the kidney with reported prevalence between 1 in 600 and 1 in 400. A typical HSK has two lower poles fused across the midline in front of the abdominal aorta just below the origin of the inferior mesenteric artery. Very rarely, the upper poles may fuse resulting in a reverse HSK. It is more common in males than in females, but no definite racial or genetic predilection has been established. The HSK is frequently associated with other congenital anomalies, the most common being vascular anomalies. This report describes HSK in a 73-year-old male cadaver, with triple renal arteries and aberrant right testicular artery originating from the ipsilateral renal artery and bilateral extra-renal calyces. Although rare in occurrence, a surgeon must bear in mind that such a combination of anomalies may pose technical difficulties during open or laparoscopic abdominal surgeries.